ASP.NET 4 24-hour trainer - Wright, Toi B. (Wrox, 2010)
"Welcome to the video portion of ASP.NET 4 24-Hour Trainer. This unique book-and-video package introduces ASP.NET 4 to programmers. Microsoft ASP.NET allows you to build dynamically generated Web pages from database content. Written by a well-known authority on ASP.NET, this book-and-video package is an ideal place to start learning about the capabilities of ASP.NET 4. Each lesson covers both the ASP.NET Web Forms Framework and the ASP.NET MVC 2 Framework and is designed to teach you the fundamentals of the topic before progressing to a step-by-step tutorial. An instructional video for each of the 48 tutorials is provided on the video that accompanies the book. ASP.NET 4 24-Hour Trainer is an exceptional book-and-video package ideal for everyone from beginners to more advanced developers."--Resource description page.